Study of composite plate traveling in water containing Ice Equivalent Objects. (January 2016) - Kwon, Y.W.; Bolstad, S.H.; Didoszak, J.M.; Rodriguez, J.A.
Abstract: An experimental study was conducted for a composite plate traveling in water containing Ice Equivalent Objects (IEO) in order to investigate the drag force exerted on the composite plate as well as its structural response. This study considered both fluid–structure interaction (FSI) as well as solid body interaction. The plate was partially submerged so as to interact with the IEO. As test parameters, the traveling speed and the orientation angle of the plate were changed, and the coverage density of the IEO was also varied. Both drag force and the strain response of the plate were measured when the plate was in either the steady-state or accelerating transient motion. In addition, a high speed camera was utilized to capture the interaction among the composite plates, IEO, and water flow. Computer modeling and simulation was also conducted for some simple cases in order to better aid understanding. The results showed that with the inclusion of the IEO, not only was there an increase in the total drag forces but also a difference in the resulting deformed shapes of the plates. As a result, strain measurements at different locations did not vary proportionally resulting from the IEO.